Cumulation of cross-section surveys: Evaluation of alternative concepts for the cumulated Continuous Household Budget Surveys (LWR) 1999 until 2003 compared to the Sample Survey of Income and Expenditures (EVS) 2003 - Joachim Merz; Henning Stolze (Institute for the Study of Labor (IZA), 2010)
With the development of household budget systems and with regard to the requirements of the European Union with new EU-SILC approaches, the cumulation of cross-section surveys to an integrated information system is recently discussed and required. In particular the reconstruction of household budget surveys should deliver yearly results as well multi-annual sufficient large samples to allow in depth analyses. This study contributes by a general conceptual foundation of the cumulation of cross-sections and an application which in particular evaluates the new cumulation concept with actual large official samples: the cross sectional cumulation of five yearly Continuous Household Budget Surveys (Laufende Wirtschaftsrechnungen, LWR) which will be compared to the large quinquennial Sample Survey of Income and Expenditures (Einkommens- und Verbrauchsstichprobe, EVS) of the German Federal Statistical Office. Therewith the sensitivity of the cumulation concept with its alternatives is evaluated for private household consumption expenditures of selected expenditure groups. A recommendation concludes.
Keywords: C42; C81; D10; E20; 330; cumulation of cross sections; temporary cumulation; adjustment by information theory; consumption expenditures; Continuous Household Budget Surveys (Laufende Wirtschaftsrechnungen; LWR); Sample Survey of Income and Expenditures (Einkommens- und Verbrauchsstichprobe; EVS) of the German Federal Statistical Office; Verbraucherausgaben; Laufende Stichprobenerhebung; Haushaltsbudget-Statistik; Vergleich; Deutschland